2004
DOI: 10.1002/ccd.20036
|View full text |Cite
|
Sign up to set email alerts
|

Randomized study of the safety and clinical utility of rotational angiography versus standard angiography in the diagnosis of coronary artery disease

Abstract: This study evaluates the safety and clinical utility of rotational angiography in the diagnosis of coronary artery disease. High-speed rotational angiography is a newly available angiographic modality that gives a dynamic multiple-angle perspective of the coronary tree during a single contrast injection. We prospectively randomized 56 patients referred for diagnostic coronary angiography to either standard or rotational angiography. Contrast and radiation utilization were compared between the two groups. The n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
35
3

Year Published

2004
2004
2013
2013

Publication Types

Select...
9
1

Relationship

7
3

Authors

Journals

citations
Cited by 70 publications
(42 citation statements)
references
References 12 publications
4
35
3
Order By: Relevance
“…This assures that the rotations are centered and that the images are calibrated so that pixel size is known, quantitative measurements are possible, and images are appropriate for 3D reconstruction. The first randomized, controlled study comparing coronary RA with conventional angiography for diagnostic coronary exams was conducted in 2004 [2], proving RA as a valid technique with the capability to complement and potentially replace certain roles of conventional static-view coronary angiography. In coronary angiography, it has been shown that rotational angiography can reduce radiation dose and contrast loads as compared with conventional angiography [3][4][5].…”
Section: Introductionmentioning
confidence: 99%
“…This assures that the rotations are centered and that the images are calibrated so that pixel size is known, quantitative measurements are possible, and images are appropriate for 3D reconstruction. The first randomized, controlled study comparing coronary RA with conventional angiography for diagnostic coronary exams was conducted in 2004 [2], proving RA as a valid technique with the capability to complement and potentially replace certain roles of conventional static-view coronary angiography. In coronary angiography, it has been shown that rotational angiography can reduce radiation dose and contrast loads as compared with conventional angiography [3][4][5].…”
Section: Introductionmentioning
confidence: 99%
“…Off line 3-D coronary angiography computer reconstructions have been available and their algorithms validated for standard imaging and rotational angiography [6,7]. While rotational angiography has been shown to decrease contrast and radiation dosage during diagnostic catheterizations, it has no direct advantage over standard imaging based 3-D modeling [8,9]. When rotational angiography is performed, two different FOV are often used (9 inches or 7 inches) to allow a complete representation of the coronary tree.…”
Section: Discussionmentioning
confidence: 99%
“…C-arm CT is emerging as a novel modality that can acquire 3D CT-like volumes directly in the OR in the same coordinate system as 2D fluoroscopy, which overcomes the need for 2D/3D registration. For most procedures, the patients are older and therefore, a safe execution of the procedure is the dominating factor [3]. Some methods work directly on the C-arm CT images [4] to extract patient-specific models for procedure guidance.…”
Section: Introductionmentioning
confidence: 99%